Hydrogeomorphic characterization and classification of Pacific Northwest mountain streams for biomonitoring - Cuhaciyan, Christopher O., author; Bledsoe, Brian P., advisor; Dean, Denis J., committee member; Wohl, Ellen E., committee member; Watson, Chester C., committee member (Colorado State University. Libraries, 2006)
Biomonitoring using benthic macroinvertebrates has become the prevailing technique for assessing stream health in the United States. Because pre-disturbance biological conditions are rarely known, a reference site approach is often used to determine the extent of stream degradation. Ecoregions are the predominant spatial units within which stream reference conditions are developed, but they neglect important valley- and reach-scale influences on stream habitats. Few existing classifications integrate hydrologic and geomorphic (i.e., hydrogeomorphic) typologies and none explicitly describe physical processes and boundary conditions of relevance to stream biotic assemblages. I used a geographical information system (GIS) to describe hydrologic regimes and geomorphic boundary conditions at 222 minimally-disturbed U. S. Environmental Protection Agency biomonitoring sites in mountainous ecoregions of the Pacific Northwest. Innovative models were developed to predict mountain channel stream types and median substrate size. I applied these multi-scale metrics to develop a priori (without biological calibration) and a posteriori (biologically calibrated) classifications of biomonitoring sites and compared them to geographically-dependent classifications including Level III ecoregions. Field-measured metrics were included in a set of a posteriori models to test for potentially important reach-scale habitat characteristics not accounted for in the GIS-developed metrics. Cluster analyses provided a basis for spatially-neutral classifications based on biological data. Similarity in stream insect assemblages within and among classes was used to develop quantitative measures of classification strength for comparing classification performance. A priori classifications outperformed ecoregions in 11 of 18 comparisons, indicating that hydrologic and geomorphic classifications can partition biological variability better than ecoregions, often with fewer classes. Classification tree models resulted in classification strengths as high as 90% of the maximum attainable. Valley-scale metrics describing floodplain presence, specific stream power, peak flows, and low flows were consistently strong predictors in classification trees. The hydrogeomorphic classifications developed provide a framework for identifying relatively homogeneous habitat types sustaining comparable stream insect assemblages and support stream-habitat restoration by providing hydrologic and geomorphic habitat endpoints to target for ecological restoration. GIS-derived hydrologic and geomorphic metrics provide a basis for mapping multi-scaled hydrogeomorphic settings and putative habitat types across entire landscapes, and a framework for process-based stratification in biomonitoring designs.
Keywords: ecology; hydrology; civil engineering; hydrologic sciences